Meaningful life dalam Novel 37 Jam: Kajian psikologi positif Martin Seligman - Putri, Dwi Ananda (Maliki Interdisciplinary Journal, 2026)
This study aims to describe and analyze the representation of a meaningful life in the novel 37 Jam by Stanley Meulen using the perspective of positive psychology proposed by Martin Seligman. The novel portrays the emotional journey of its two main characters, Ari and Widi, as they strive to save their mother amid a tense and critical situation. This research employs a descriptive qualitative method, with the primary data source taken from the text of the novel, while supporting data are obtained from literature relevant to positive psychology and literary studies. The results of the analysis show that meaningful life in the novel is manifested through three main aspects: hope, love, and gratitude. In addition to these individual aspects, the positive relationship between Ari and Widi also plays an important role in shaping the meaning of life, particularly through the development of a warmer relationship, emotional support, and their ability to negotiate conflicts constructively. The novel demonstrates that the meaning of life is constructed through sacrifice, family commitment, and the values inherited from the figure of a mother. These findings emphasize that experiences of crisis can become a space for psychological transformation, enabling individuals to discover meaning, resilience, and life purposes that extend beyond themselves. These findings emphasize that experiences of crisis can become a space for psychological transformation, enabling individuals to discover meaning, resilience, and life purposes that extend beyond themselves.